Impact of Electronic Channels and Home Service During the Covid-19 Pandemic - Alvarado Martínez, Holger (2021)
The main objective of this article is to determine the impact of electronic channels and home service during the Covid-19 pandemic, whose specific purposes are focused on defining the social impacts that both tools generated during quarantine, as well as identifying the economic impacts in the face of this critical situation that the locality, the nation and the world are currently experiencing. For this purpose, descriptive research was applied, because it is directly associated with the quantitative approach and the field modality, also using the survey questionnaire to users of this type of services, who remained in their homes during the quarantine. The results obtained showed: as the main social impacts due to the use of electronic channels and home service, the minimization of contagion with the coronavirus infection, by staying in the home, respecting social distancing, not exposing oneself in a health, educational establishment , nor labor, however, there is some dissatisfaction with the virtual classes and for breach of strict biosafety regulations in the personnel dedicated to home delivery; while the main economic impacts were the maintenance of jobs with the same salary they had before the pandemic, the revitalization of the economy, because these organizations contributed to the generation of economic development in the town of Quevedo, during quarantine. In conclusion, most of the observed impacts are positive, both in the social and economic aspects, therefore, it is necessary to carry out more research on this topic, to strengthen virtual services and home delivery of goods in Quevedo, in the time to come, after the coronavirus.